Complex fluid flow in microchannels and heat pipes with enhanced surfaces for advanced heat conversion and recovery systems - Moita, Ana Sofia (2022)
This paper addresses a multiscale approach for heat recovery systems, used in two distinct applications. In both applications, a microscale approach is used (microchannel heat sinks and heat pipes) for macroscale applications (cooling of a photovoltaic—PV cell), and the thermal energy of exhaust gases of an internal combustion engine is used for thermoelectric generators with variable conductance heat pipes. Several experimental techniques are combined such as visualization, thermography with high spatial and temporal resolution, and the characterization of the flow hydrodynamics, such as the friction losses. The analysis performed evidences the relevance of looking at the physics of the observed phenomena to optimize the heat sink geometry. For instance, the results based on the dissipated heat flux and the convective heat transfer coefficients obtained in the tests of the microchannel-based heat sinks for cooling applications in PV cells show an improvement in the dissipated power at the expense of controlled pumping power, for the best performing geometries. Simple geometries based on these results were then used as inputs in a genetic algorithm to produce the optimized geometries. In both applications, the analysis performed evidences the potential of using two-phase flows. However, instabilities at the microscale must be accurately addressed to take advantage of liquid phase change. In this context, the use of enhanced interfaces may significantly contribute to the resolution of the instability issues as they are able to control bubble dynamics. Such an approach is also addressed here.